2022
DOI: 10.3389/fbioe.2022.1003484
|View full text |Cite
|
Sign up to set email alerts
|

Natural biopolymer scaffold for meniscus tissue engineering

Abstract: Meniscal injuries caused by trauma, degeneration, osteoarthritis, or other diseases always result in severe joint pain and motor dysfunction. Due to the unique anatomy of the human meniscus, the damaged meniscus lacks the ability to repair itself. Moreover, current clinical treatments for meniscal injuries, including meniscal suturing or resection, have significant limitations and drawbacks. With developments in tissue engineering, biopolymer scaffolds have shown promise in meniscal injury repair. They act as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 112 publications
0
7
0
Order By: Relevance
“…However, this treatment method inevitably causes damage to the normal meniscus structure. Therefore, the decellularized meniscus scaffold came into being. …”
Section: The Application Of Decellularized Scaffolds In Tissue Engine...mentioning
confidence: 99%
“…However, this treatment method inevitably causes damage to the normal meniscus structure. Therefore, the decellularized meniscus scaffold came into being. …”
Section: The Application Of Decellularized Scaffolds In Tissue Engine...mentioning
confidence: 99%
“…10,13 Owing to its low immunogenicity and high biocompatibility, this collagen I implant provides a biodegradable scaffold that is replaced by patient-synthesized tissue. 14 CMI has been approved as a safe biomaterial by European and US regulatory agencies; 11,13,15 however, therapeutic failures and lack of functional improvement have been reported. 12,16 Because of these limitations and the high incidence of meniscal injuries, 17 meniscal substitutes with clinical applications must continue to be developed and characterized.…”
Section: Introductionmentioning
confidence: 99%
“…Although several clinical studies of meniscus substitutes have been conducted over the years, few have been approved for clinical application in humans. Among these is the collagen meniscus implant (CMI), which is used for the repair of segmental meniscal defects after arthroscopic partial meniscectomy. , Owing to its low immunogenicity and high biocompatibility, this collagen I implant provides a biodegradable scaffold that is replaced by patient-synthesized tissue . CMI has been approved as a safe biomaterial by European and US regulatory agencies; ,, however, therapeutic failures and lack of functional improvement have been reported. , Because of these limitations and the high incidence of meniscal injuries, meniscal substitutes with clinical applications must continue to be developed and characterized.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, meniscal scaffolds have been studied for meniscal regeneration using tissue engineering techniques. [15][16][17] A meniscal scaffold could be used for replacing degenerated menisci and preserve the biomechanical properties of the meniscus. Although Zaffagnini et al 7 reported that treatment with a scaffold had been superior to partial meniscectomy, these scaffolds did not yield long-term regeneration.…”
Section: Introductionmentioning
confidence: 99%